Biological features of working bees in wintering bee colonies on different forage - Шамро, Л. П.; Шамро, Т. М. (Scientific Progress & Innovations, 2013)
A comparative study of anatomical and physiological characteristics of bees in bee colonies (the concentration of protein in the hemolymph, the degree of pharyngeal glands and fat body) that wintered in the honey and sugar feed, during the autumn-winter-early spring period of their detention was done. It was found that during the replenishment of forage supplies in winter with feed sugar concentration of protein in the hemolymph of bees falls to 48.15 against 72.05 g/l in the media families (P<0,01). Later - during the winter stay and to replacing wintered bees into summer - it is always slightly lower than in families who eat honey in winter. The degree of development of pharyngeal glands and fat body during the study period is consistently (uncertainly) lower in bee families that wintered on sugar feed.